Application of teachers’ knowledge of socratic questioning in developing efl critical thingking skills among omani post-basic learners - Moosa Ahmed Hassan Bait Ali Sulaiman (2019)
With the premise that effective use of Socratic Questioning in instructional practices is of vital importance in EFL/ESL classrooms, this study was undertaken to investigate application of Omani EFL teachers’ knowledge of Socratic Questioning (SQ) on Students’ Critical thinking (CT) in post basic schools. This study is conducted in two phases of investigation. Phase I examined the correlation between teachers’ knowledge and actual use of SQ. Phase II study investigated the application of Omani EFL teachers’ knowledge of SQ on students’ CT in post-basic schools. The present study made an attempt to (a) Determine the relationship between teachers’ knowledge of SQ and their actual use of SQ. (b) Ascertain whether there is any statistically significant difference between mean scores of those who are taught through SQ and those who are taught CT skills in a normal setting. (c) Identify CT strategies, the students were able to develop and apply at the end of the intervention phase. A total of 230 EFL teachers, which comprises a 100% of the total population of all EFL post-basic female teachers in Dhofar region of Oman, participated in this study. The multi-method procedures and data analyses showed that (a) There is a strong positive relationship between teachers’ perceived knowledge and their actual use of SQ; (b) There are significant differences between mean scores of those who were taught CT through SQ and those who were taught CT skills in a normal setting; (c) There is a clear evidence to suggest that students in the experimental group were able to develop effective CT strategies during the intervention phase. The findings of this study offer a number of implications: (a) For instructional practice that involves the teachers and students; (b) For policy and decision makers; and (c) For syllabus designers and testing and evaluation. In addition, it identifies and proposes certain areas related to pedagogy for future research.